LINGKUNGAN BISNIS DAN BUDAYA ORGANISASI: PERANANNYA TERHADAP STRATEGI BISNIS DAN KINERJA BANK UMUM SYARIAH - Arief Purwanto (University of Merdeka Malang, 2014)
The purposes of the study were to examine and to prove empirically the role of business environment, organization culture in producing the right business strategy and improving the performance of Islamic Commercial Bank (Bank Umum Syariah/BUS) organizations. The population was all BUS branch offices in East Java, consisting of 34 branch offices and this study was a census study. The study was analyzed using Partial Least Square (PLS) with SmartPLS software. The result of the study showed that: (1) The business environment had a direct role in strengthening organization culture and improving business strategy, but did not have a direct significant impact in improving the organization’s performance. (2) The stronger organization’s culture had an important role in improving business strategy, but did not have a direct significant impact in improving the organization’s performance (3) The right business strategy would improve the organization’s performance.